Solve the following system of equations: 3x − 2y = 6 6x − 4y = 12

(2) Answers

3x-2y=(6)(6x)-4y=12 First, you would add -2y on both sides and get 3x=(6)(6x)-2y=12. Then, you would multiply 6 and 6x and get 3x=36x-2y=12 Then, you would subtract 3x on both sides: 33x-2y=12 Then, to get rid of 33x, you would multiply everything by 33: -2y=369 Then you didvide both sides by -2 and you get y= -198 If you wanted to get rid of -2y, you would do the same thing of what you did by getting rid of 33x except for multiplying everything by -2.


multiple the top equation by negative 2 then add the equations hope this helps

Add answer